An elderly lady with multiple blisters all over the body: Hailey Hailey Disease - Sharma, Tanzina Nuhat; Saha, Lima; Sharif, Mohiuddin; Haque, Md Mahfuzul; Amin, Md Robed (Bangladesh Journal of Medicine, 2019)
Hailey-Hailey disease (HHD) is an autosomal-dominant genodermatosis, associated with abnormal epithelial cell adhesion due to altered calcium metabolism. Clinical features involve painful red blisters, erosions, fissured and hypertrophic plaques predominantly in the intertriginous areas. Heat, friction, minor trauma, superimposed bacterial or viral infection can aggravate the condition. Here, we report a case of a 50-year old lady with no previous family history presented with severe attack of HHD since last 5 months. Histology showed acantholysis of keratinocytes resembling characteristic dilapidated brick wall appearance in the epidermis layer of skin which helped for the confirmed diagnosis. Bangladesh J Medicine Jan 2020; 31(1) : 29-32